CHARACTER OF СYBERPUNK IN MODERN INFORMATION SPACE - Окорокова, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article is sanctified to research of a сyberpunk in modern information space. The aim and tasks. An author pays attention to the transformation of a сyberpunk: beginning as a genre of literature, in these days it has already turned out into a character, a symbol of a virtual man. Research methods. The virtualization of society assisted forming of the model of virtual personality. In a great deal it explains that circumstance, that often a modern man is already unable to distinguish the real from virtual, as computer technologies are subordinated swift rates to the soba all large areas of human existence. "Homo of virtualis" is oriented only to virtual-ness, as the world his activity passes in that. Creating the virtual worlds, perfecting them, we at conscious level all anymore submerge in artificial reality, all more often breaking a secret with social. Research results. An author marks that the prime example of virtual man, both literary works and cinemas are dedicated that, is a cyberpunk. In the modern culture of a cyberpunk often personifies by the fantas-tic worlds of future, mostly anti-utopian character (for example, as a result of catastrophe: ecological or technotronic; evolutions of mod-ern society to such measure, when works take power, cyborgization of man and other). From here pessimism that dominates in society of a сyberpunk, the main task of that is opposition to the existent frame of society, replacing a corporation that destroys human roots in society a technique. Conclusion. This is one of main problems of modern science - man initiates desobjectivation, transformation of him from Homo sapiens to "Homo machine", "Homo virtualis" as a model of a new man, different from the natural essence that carries in itself the projection of technogenic.